FoxG1 Directly Represses Dentate Granule Cell Fate During Forebrain Development - Han, Xiao; Gu, Xiaochun; Zhang, Qianqian; Wang, Qingxia; Cheng, Yao; Pleasure, Samuel J.; Zhao, Chunjie (Frontiers in Cellular Neuroscience, 2018)
The cortex consists of hundreds of neuronal subtypes that are organized into distinct functional regions; however, the mechanisms underlying cell fate determination remain unclear. Foxg1 is involved in several developmental processes, including telencephalic patterning, cell proliferation and cell fate determination. Constitutive disruption of Foxg1 leads to the transformation of cortical neurons into Cajal-Retzius (CR) cells, accompanied by a substantial expansion of the cortical hem through the consumption of the cortex. However, rather than the induction of a cell fate switch, another group has reported a large lateral to medial repatterning of the developing telencephalon as the explanation for this change in cell type output. Here, we conditionally disrupted Foxg1 in telencephalic progenitor cells by crossing Foxg1fl/fl mice with Nestin-CreERTM mice combined with tamoxifen(TM) induction at distinct developmental stages beginning at E10.5 to further elucidate the role of FoxG1 in cell fate determination after telencephalon pattern formation. The number of dentate gyrus (DG) granule-like cells was significantly increased in the cortex. The increase was even detected after deletion at E14.5. In vivo mosaic deletion and in vitro cell culture further revealed a cell-autonomous role for FoxG1 in repressing granule cell fate. However, the cortical hem, which is required for the patterning and the development of the hippocampus, was only slightly enlarged and thus may not contribute to the cell fate switch. Lef1 expression was significantly upregulated in the lateral, cortical VZ and FoxG1 may function upstream of Wnt signalling. Our results provide new insights into the functions of FoxG1 and the mechanisms of cell fate determination during telencephalic development.